The Universal Childcare Program in Quebec: An Analysis of the Time Parents Spend with their Children - Francis, Lama (Université d'Ottawa | University of Ottawa, 2014)
Quebec’s Universal Childcare Program (UCP) was implemented in 1997 to increase women’s labour force participation, increase children’s readiness for school, and give equal opportunities for parents to get childcare for their children at an affordable price. The policy did increase mothers’ labour force participation rate; however, critics of the policy argue that the policy has (negatively) affected children’s cognitive development and diminished the quality of daycare service in the province. This paper uses a difference-in-difference method and time use data from General Social Surveys (GSS) to estimate the effect of the policy on the time parents spent taking care of children (less than 5 years old), playing, reading and reprimanding them. The analysis yields no significant difference in the time fathers and single mothers spent with their children, however, a statistically significant decrease in time mothers of two-parent households spent playing with their children and an increase in reading time is found.